Mortality rates among vaccinated and unvaccinated covid19 patients in Duhok hospitals, Kurdistan Region, Iraq - Wahab Farho Tahlo; Ameen Mosa Mohammad (Advanced Medical Journal)
Background and objectives: The corona virusvaccines are important in controlling the pandemic. In Kurdistan Region of Iraq three types of vaccines are available; Pfizer, AstraZeneca and SinoPharm. The objectiveof the study was to determine the effect of vaccine on severity and mortality rate among Covid-19 cases in Duhok, Iraq.